Our cosmic habitat - Rees, Martin J., 1942- (Princeton, N.J. : Princeton University Press, 2001)
Astronomer Martin Rees ponders a question posed by Albert Einstein who wondered whether God could have made the world any differently, and assuming the answer is yes, offers his meditations upon the origins of the universe and the laws of physics.
Includes bibliographical references (p. 187-195) and index.
Booklist.
Science Books & Films (A.A.A.S.).
University Press Titles (A.A.S.L./P.L.A.).
Adult
Keywords: Cosmology; Cosmology